IL-6 inhibition with ziltivekimab in patients at high atherosclerotic risk (RESCUE): a double-blind, randomised, placebo-controlled, phase 2 trial. Issue 10289 (29th May 2021) - Ridker, Paul M; Devalaraja, Matt; Baeres, Florian M M; Engelmann, Mads D M; Hovingh, G Kees; Ivkovic, Milana; Lo, Larry; Kling, Douglas; Pergola, Pablo; Raj, Dominic; Libby, Peter; Davidson, Michael; et al.
Summary: Background: IL-6 has emerged as a pivotal factor in atherothrombosis. Yet, the safety and efficacy of IL-6 inhibition among individuals at high atherosclerotic risk but without a systemic inflammatory disorder is unknown. We therefore addressed whether ziltivekimab, a fully human monoclonal antibody directed against the IL-6 ligand, safely and effectively reduces biomarkers of inflammation and thrombosis among patients with high cardiovascular risk. We focused on individuals with elevated high-sensitivity CRP and chronic kidney disease, a group with substantial unmet clinical need in whom previous studies in inflammation inhibition have shown efficacy for cardiovascular event reduction. Methods: RESCUE is a randomised, double-blind, phase 2 trial done at 40 clinical sites in the USA. Inclusion criteria were age 18 years or older, moderate to severe chronic kidney disease, and high-sensitivity CRP of at least 2 mg/L. Participants were randomly allocated (1:1:1:1) to subcutaneous administration of placebo or ziltivekimab 7·5 mg, 15 mg, or 30 mg every 4 weeks up to 24 weeks. The primary outcome was percentage change from baseline in high-sensitivity CRP after 12 weeks of treatment with ziltivekimab compared with placebo, with additional biomarker and safety data collected over 24 weeks of treatment. Primary analyses were done in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of assigned treatment. The trial is registered with ClinicalTrials.gov, NCT03926117 . Findings: Between June 17, 2019, and Jan 14, 2020, 264 participants were enrolled into the trial, of whom 66 were randomly assigned to each of the four treatment groups. At 12 weeks after randomisation, median high-sensitivity CRP levels were reduced by 77% for the 7·5 mg group, 88% for the 15 mg group, and 92% for the 30 mg group compared with 4% for the placebo group. As such, the median pairwise differences in percentage change in high-sensitivity CRP between the ziltivekimab and placebo groups, after aligning for strata, were –66·2% for the 7·5 mg group, –77·7% for the 15 mg group, and –87·8% for the 30 mg group (all p<0·0001). Effects were stable over the 24-week treatment period. Dose-dependent reductions were also observed for fibrinogen, serum amyloid A, haptoglobin, secretory phospholipase A2, and lipoprotein(a). Ziltivekimab was well tolerated, did not affect the total cholesterol to HDL cholesterol ratio, and there were no serious injection-site reactions, sustained grade 3 or 4 neutropenia or thrombocytopenia. Interpretation: Ziltivekimab markedly reduced biomarkers of inflammation and thrombosis relevant to atherosclerosis. On the basis of these data, a large-scale cardiovascular outcomes trial will investigate the effect of ziltivekimab in patients with chronic kidney disease, increased high-sensitivity CRP, and established cardiovascular disease. Funding: Novo Nordisk.